Pengaruh Slack Resources, Profitabilitas, dan Media Exposure terhadap Pengungkapan Corporate Social Responsibility - Nazar, Mohamad Rafki; Istiqomah, Nur Hidayah (SAFE-Network, 2023)
The purpose of this study is to determine the effect of slack resources, profitability, and media exposure on corporate social responsibility disclosure (study of companies listed on the kompas 100 index in 2018-2021). This research is descriptive and verification research. The population in the study totalled 100 companies listed in the Kompas 100 Index for the 2018-2021 period. In this study, the data analysis used a panel data regression model and was processed using Eviews 12 software. The results of this study, namely the value of corporate social responsibility disclosure, show that the majority of Kompas 100 Index companies in 2018-2021 do not have a good level of CSR disclosure. Slack resources as measured using Short Term Slack which is calculated using the value of cash and cash equivalents during 2018-2021 according to research observations, the majority of companies are quite efficient in receiving cash and cash equivalents. Profitability as measured using ROA during 2018-2021 according to research observations, the majority of companies have not used assets efficiently enough to generate profits. Media exposure according to research observations, the majority of Kompas 100 Index companies in 2018-2021 have disclosed corporate social responsibility activities on the company's official website. Based on simultaneous hypothesis testing, it is concluded that the slack resources, profitability, and media exposure variables have an influence on corporate social responsibility disclosure. Based on the coefficient of determination, the independent variables consisting of slack resources, profitability, and media exposure are able to explain the dependent variable, namely the disclosure of corporate social responsibility by 72.33%. Based on partial hypothesis testing, the results obtained Slack resources, Profitability, Media Exposure have a positive effect on the disclosure of corporate social responsibility.